Pharmaceuticals and endocrine disruptors in raw and cooked seafood from European market: Concentrations and human exposure levels. (October 2018) - Álvarez-Muñoz, Diana; Rodríguez-Mozaz, Sara; Jacobs, Silke; Serra-Compte, Albert; Cáceres, Nuria; Sioen, Isabelle; Verbeke, Wim; Barbosa, Vera; Ferrari, Federico; Fernández-Tejedor, Margarita; Cunha, Sara; Granby, Kit; et al.
Abstract: Pharmaceuticals (PhACs) and endocrine disrupting compounds (EDCs) are chemicals of emerging concern that can accumulate in seafood sold in markets. These compounds may represent a risk to consumers through effects on the human reproductive system, metabolic disorders, pathogenesis of breast cancer or development of microbial resistance. Measuring their levels in highly consumed seafood is important to assess the potential risks to human health. Besides, the effect of cooking on contaminant levels is relevant to investigate. Therefore, the objectives of this research were to study the presence and levels of PhACs and EDCs in commercially available seafood in the European Union market, to investigate the effect of cooking on contaminant levels, and to evaluate the dietary exposure of humans to these compounds through seafood consumption. A sampling survey of seafood from 11 European countries was undertaken. Twelve highly consumed seafood types were analysed raw and cooked with 3 analytical methods (65 samples, 195 analysis). PhACs were mostly not detectable or below quantification limits in seafood whereas EDCs were a recurrent group of contaminants quantified in the majority of the samples. Besides, cooking by steaming significantly increased their levels in seafood from 2 to 46-fold increase. Based on occurrence and levels, bisphenol A, methylparaben and triclosan were selected for performing a human exposure assessment and health risk characterisation through seafood consumption. The results indicate that the Spanish population has the highest exposure to the selected EDCs through seafood consumption, although the exposure via seafood remained below the current toxicological reference values.